Dissecting the Hack - Street, Jayson (Elsevier, 2011)
Dissecting the Hack is one heck of a ride! Hackers, IT professional, and Infosec aficionados (as well as everyday people interested in security) will find a gripping story that takes the reader on a global trip through the world of computer security exploits. One-half thriller, one-half reference, each provides context for the other. Together they will show you how to see the digital world just below the surface of daily life.